Cyclic simple shear properties of unsaturated residual soils - Chin, Kheng Boon (2013)
In Singapore, two thirds of the land area is underlain by residual soils. One distinct characteristic of residual soils is its unsaturated nature. The relationships of shear modulus and damping ratio with shear strain for residual soils may differ from transported soils and have not been fully investigated. This study aims to investigate shear stiffness and damping ratio properties of residual soils under cyclic simple shear loading in both saturated and unsaturated conditions.